AI-as-a-Service: Transforming Cloud-Based Machine Learning - AI Governance (Utilitas Mathematica, 2025)
The trends have seen the rise of a new transformative paradigm called Artificial Intelligence-as-a-service (AIaaS), which is democratizing the availability of machine learning capabilities across the organizational line. Entities of any size can use advanced AI through this cloud-based model, without making sizeable investments into infrastructure and skills to operate it. The article looks at the architectural pillars of AIaaS, scrutinizing its four-layered structure that consists of data ingestion, model management, inference serving, and monitoring functionalities. It compares top platforms such as AWS SageMaker, Google Vertex AI, Microsoft Azure ML, and Hugging Face and points out their unique strategies in machine learning operations. It presents the most important strategic benefits of adopting AIaaS, like aster deployment, scale elasticity, cost, and democratization, but recognizes that the most prominent obstacle to implementation is model interpretability, performance optimization, security, compliance, and lastly model maintenance. Looking ahead, the article examines new space trends that will influence the further development of AIaaS, such as the feature of autoML integration, federated learning methods, model marketplace, governance systems, and self-improving AI models, respectively, opening the perspective of AIaaS as a basis of intelligent systems in various industries.